Green waqf and sustainable development: cases in Malaysia and Indonesia - Duasa, Jarita; Munir, Misbahul (Routledge, Taylor & Francis Group, 2025)
The use of Islamic social financial instruments of Waqf to support eco-friendly activities is presented in this chapter. Green finance through Waqf fund is discussed in the context of Malaysia and Indonesia. The study focuses on two Waqf institutions in Malaysia and two Waqf institutions in Indonesia to understand the green Waqf practices adopted by the Waqf institutions in the selected countries. The study uses secondary data obtained from the selected Waqf institutions. The data are used to identify and compare the organizational setup, channel of accountability, activities particularly related to environment, renewable resources and related as well as beneficiaries of selected Waqf institutions. The Waqf institutions involved in the study include two Waqf entities in Malaysia namely Yayasan Waqf Malaysia (YWM) and Waqaf An-Nur Corporation Berhad, while in Indonesia are Badan Wakaf Indonesia (BWI) and Tabung Wakaf Dompet Dhuafa. The experiences from the studied Waqf institutions contribute towards highlighting recommended best practices by Waqf institutions in enhancing the management and efficiency of Waqf institutions as regard to green Waqf in Malaysia and Indonesia.